2020
DOI: 10.1002/adma.201907164
|View full text |Cite
|
Sign up to set email alerts
|

Rafting‐Enabled Recovery Avoids Recrystallization in 3D‐Printing‐Repaired Single‐Crystal Superalloys

Abstract: The repair of damaged Ni‐based superalloy single‐crystal turbine blades has been a long‐standing challenge. Additive manufacturing by an electron beam is promising to this end, but there is a formidable obstacle: either the residual stress and γ/γ  ′ microstructure in the single‐crystalline fusion zone after e‐beam melting are unacceptable (e.g., prone to cracking), or, after solutionizing heat treatment, recrystallization occurs, bringing forth new grains that degrade the high‐temperature creep properties. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…However, , but so far limitedonly a few studies have been reported in laser 3D printed directionally solidified and single crystalline Ni-based superalloys with high Ti/Al contents and thus high γ′ fraction, especially without post processing heat treatment [11,17] γ′-strengthened Ni-based superalloys.. reported results on 3D printed Ni-based superalloys are scarce. In particular, detailed knowledge of the dislocation type and distribution, and how the chemical inhomogeneity associated with the cellular structure influences the size, morphology, and phase of the strengthening precipitates is essential to understand the mechanical performance of 3D printed Ni-based superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…However, , but so far limitedonly a few studies have been reported in laser 3D printed directionally solidified and single crystalline Ni-based superalloys with high Ti/Al contents and thus high γ′ fraction, especially without post processing heat treatment [11,17] γ′-strengthened Ni-based superalloys.. reported results on 3D printed Ni-based superalloys are scarce. In particular, detailed knowledge of the dislocation type and distribution, and how the chemical inhomogeneity associated with the cellular structure influences the size, morphology, and phase of the strengthening precipitates is essential to understand the mechanical performance of 3D printed Ni-based superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 8(a), HAZ grains are visualized in different colors from the substrate and cladding layers, demonstrating the occurrence of recrystallization in the HAZ after solution heat treatment due to the large amount of stored energy from the high density of dislocations (Chen et al, 2020). It is observed in Fig.…”
Section: Orientation and Misorientation Analysismentioning
confidence: 85%
“…The average FWHM of all indexed Laue peaks in angular space is taken to describe the diffraction peak shape. With these powerful software packages, mXRD has been applied to the investigation of phase identification and structural evolution of micro-/nanocrystals (Guo et al, 2011;Strelcov et al, 2012;Dejoie et al, 2014), orientation mapping of single-or polycrystalline materials (Chen et al, 2010;Ma et al, 2015), transient and residual strain/stress measurement in engineering and natural materials (Chen et al, 2009(Chen et al, , 2015(Chen et al, , 2020Li, Xie et al, 2018), and evaluation of dislocation type, arrangement and density by analyzing the Laue peak shape (Lupinacci et al, 2015;. In these typical applications of the mXRD technique, it is found that the functionalities, such as 2D map plotting, misorientation computing, grain boundary characterization and strain/stress distribution visualization, need to be further enhanced for general users.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] But, these indirect methods do not provide enough decentralized information. Although various advanced micro-morphology analysis techniques such as OM, [14] SEM, [15,16] transmission electron microscopy (TEM), [17,18] and AFM [19] have been used to evaluate the dispersion state of fillers in polymer matrix, these testing methods can only get twodimensional (2D) image information of the dispersion of fillers, which cannot truly represent the macro dispersion of inorganic fillers. Computed tomography (Nano-CT) is used to research the three-dimensional (3D) dispersion of filler structures in polymer composites.…”
Section: Introductionmentioning
confidence: 99%